Analyzing and formalising land indicators of LGAF, GLII and SDGs through LADM - Chen, Mengying; Kara, Abdullah; van Oosterom, Peter; Murguia, Regina Orvananos; Gitau, John; Lemmen, Christiaan (Taylor & Francis Ltd, 2025)
Over the past fifteen years, LGAF, GLII, and SDGs frameworks have jointly shaped a complementary global land governance monitoring system. However, challenges remain in data fragmentation and standardised indicator computation. This study explores how ISO 19152 LADM provides a unified technical foundation to model and monitor global land indicators. It develops a standardised conceptual model with UML-based implementation and proposes a modular indicator computation architecture based on interface classes and reusable logic components. The proposed approach supports scalable reporting, enhances indicator operationalisation, and bridges the gap between global policy frameworks and practical land administration systems at the national level.
Keywords: Land administration; Land Administration Domain Model; ISO19152 LADM; Land Governance Assessment Framework; Global Land Indicators Initiative; Sustainable Development Goals Indicator Formalization